ÐÐ¿Ð¸Ñ‚Ð¾Ð¿ Gal-a-1,3-Gal: Ñ€Ð¾Ð»ÑŒ Ð² Ð±Ð¸Ð¾Ð»Ð¾Ð³Ð¸Ð¸ ÐºÐ»ÐµÑ‚ÐºÐ¸ Ð¸ Ñ‚Ñ€Ð°Ð½ÑÐ¿Ð»Ð°Ð½Ñ‚Ð°Ñ†Ð¸Ð¸ - Bohuslavskyi, Konstantin I.; Bozhok, Galina A.; Legach, Evgeniy I.; Furda, Igor V.; Bondarenko, Tatyana P. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2016)
Gal-a-1,3-Gal (a-Gal) epitope is a carbohydrate structure, which is expressed on cell membranes of almost all the mammals except some species of monkeys and human, as well as causes a hyperacute immune response during xenotrans-plantation. This review briefly describes the issues of the evolution of a-Gal epitope, its distribution in the kingdom of animals, biological role and problems of using prostheses of porcine origin in medical practice. For many reasons, this species of animals is the most suitable to obtain the bioprostheses of cardiac valves, vessels and bioscaffolds, however, due to the high a-Gal epitope expression in their body a special treatment to eliminate it is required. This review attempts to summarize the results on studying the a-Gal epitope expression after low-temperature treatment, since it is widely used to store bioprostheses prior to implantation. Probl Cryobiol Cryomed 2016; 26(1):3-12